Acoustic Birefringence and Poisson S Ratio Determined by Ultrasound: Tools to Follow-Up Deformation by Cold Rolling and Recrystallization - Monsalve-Gonzalez, A; Carvajal-Ortega, L; Vargas-Hernandez, y; Artigas-Abuin, A (Universidade Federal de Sao Carlos, 2017)
Poisson s ratio and birefringence, both measured by ultrasound, are used to follow the evolution of the anisotropy in ASTM A-36 steel plates cold-rolled between 5 and 50% deformation, and then subjected to recrystallization at 900 and 1000 °C. Times of flight of longitudinal and shear waves along the thickness of the plates were measured. As orthotropy increases, both birefringence and the difference between Poisson s ratios measured using a shear wave polarized along the length and another wave polarized along the width of the plate, are linearly related to the degree of deformation and cold-rolled hardness. In addition, the ultrasonic methods used clearly detected the complex changes in anisotropy produced by the austenization and recrystallization heat treatments. Thus, Birefringence or Poisson s ratio, measured by ultrasound, can be used to follow-up nondestructively changes in the anisotropy of rolled plates as a function of both, degree of deformation and recrystallization heat treatment. © 2017 Universidade Federal de Sao Carlos. All rights reserved.